Incident comorbidities and all-cause mortality among 5-year survivors of Stage I and II breast cancer diagnosed at age 65 or older: a prospective-matched cohort study - Jordan, Jennifer H.; Thwin, Soe Soe; Lash, Timothy L.; Buist, Diana S. M.; Field, Terry S.; Haque, Reina; Pawloski, Pamala A.; Petersen, Hans V.; Prout, Marianne N.; Quinn, Virginia P.; Yood, Marianne Ulcickas; Silliman, Rebecca A.; et al. (Breast cancer research and treatment, 2014)
Five-year breast cancer survivors, diagnosed after 65 years of age, may develop more incident comorbidities than similar populations free of cancer. We investigated whether older breast cancer survivors have a similar comorbidity burden 6–15 years after cancer diagnosis to matched women free of breast cancer at start of follow-up and whether incident comorbidities are associated with all-cause mortality. In this prospective cohort study, 1,361 older 5-year early-stage breast cancer survivors diagnosed between 1990 and 1994 and 1,361 age- and health system-matched women were followed for 10 years. Adjudicated medical record review captured prevalent and incident comorbidities during follow-up or until death as collected from the National Death Index. Older 5-year breast cancer survivors did not acquire incident comorbidities more often than matched women free of breast cancer in the subsequent 10 years [hazard ratio (HR) 1.0, 95 % confidence interval (95 % CI) 0.93, 1.1]. Adjusted for cohort membership, women with incident comorbidities had a higher mortality rate than those without incident comorbidities (HR 4.8, 95 % CI 4.1, 5.6). A breast cancer history continued to be a hazard for mortality 6–15 years after diagnosis (HR 1.3, 95 % CI 1.1, 1.4). We found that older breast cancer survivors who developed comorbidities had an increased all-cause mortality rate even after adjusting for age and prevalent comorbidity burden. Additionally, survivors acquire comorbidities at a rate similar to older women free of breast cancer. These results highlight the association between comorbidity burden and long-term mortality risk among older breast cancer survivors and their need for appropriate oncology and primary care follow-up.